Left ventricular mass in male adolescent athletes and non-athletes - Erling David Kaunang; Jane G. C. Metusala; Audrey M. I. Wahani (Paediatrica Indonesiana, 2014)
Background Systematic exercise leads to increased left ventricular mass, which may be misleading in a differential diagnosis of heart disease in athletes (physiologic hypertrophy versus pathologic hypertrophy). T he cause of left ventricular hypertrophy is an important risk factor in the morbidity and mortality of cardiovascular diseases.Objective To compare left ventricular mass and left ventricular hypertrophy in male adolescent athletes and non-athletes.Methods We conducted a cross-sectional, analytic study, from September to December 2012 in male adolescents aged 15-18 years. The case group included athletes from the Bina Taruna Football Club Manado, while the control group included non-athlete adolescents. All subjects underwent history-taking, physical examinations and further supporting examinations. Left ventricular mass was measured by cardiovascular echocardiography (Esaote Mylab 4.0) and calculated based on a formula. Left ventricular hypertrophy was defined as left ventricular mass of > 134 g/m2 body surface area.Results Subjects' mean left ventricular masses were 359.69 (SD 188.4; 95%CI 283.58 to 435.81) grams in the athlete group and 173.04 (SD 50.69; 95%CI 152.56 to 103.51) grams in the nonÂ· athlete group, a statistically significant difference (P=0.0001). Ventricular hypertrophy was found 76.9% compared to 11.5% in Â the non-athlete group (P= 0.0001).Conclusion Left ventricular mass in athletes is bigger than in non-athletes. In addition, left ventricular hypertrophy is more cornmon in male adolescent athletes than in non-athletes.